DRAINAGE BASIN DYNAMICS : A Geographical Perspective - Mohmadisa Hashim; Dewi Liesnoor Setyowati; Nasir Nayan (Penerbit UTHM, 2022)
This book entitles Drainage Basin Dynamics: A Geographical Perspective is conceptualized with research experience from two universities in Malaysia (Universiti Pendidikan Sultan Idris) and Indonesia (Universitas Negeri Semarang). A total of 32 researchers have contributed chapters. The research translated into chapters is based on the real experience of the author/researcher. This book provides readers with research that has been conducted in Malaysia and Indonesia with the main focus on river basins from a geographical perspective. This book summarizes research on river basins that are unlimited and can be multiplied further. A river basin is a natural entity found on the earth’s surface. Physically it is an area that is drained by the major river and its tributaries and is very important to live in it whether to humans, flora and fauna. Drainage basins are not static but dynamic because they change because of natural and human factors. However, the changes that occur in the river basin today are because of human intervention that has explored and developed the drainage basin area in the name of development. This book attempts to delve into issues related to the physical and human geography in providing dynamics that occur in a drainage basin.